Guidance and Counseling Program for Problem Solving Skills Development: A Literature Review - Nahdliyin, Choirun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The aim of learning to solve problems is to cultivate students' cognitive processes by presenting them with problem-solving tasks. Depending on the nature of the problem introduced in the classroom, problem-solving techniques may be applied either collaboratively in groups or individually. The guidance and counseling program contributes to the development of problem-solving skills by incorporating instructional methods that train students to address a range of challenges—both personal and group-related—whether tackling them independently or in collaboration. This research adopts a library research method, following the steps outlined by Zed (2014): a) formulating a general understanding of the research topic, b) seeking supporting information, c) refining the research focus, d) locating and organizing relevant reading materials, e) reading and annotating research notes, f) revisiting and augmenting reading materials, and g) reorganizing materials for the writing phase. Data sources, obtained through offline and online means such as books, journals, and articles, are systematically collected to establish a comprehensive reference database focused on studies investigating the application of guidance and counseling in the digital era. The selected timeframe for inclusion spans the last 5 years, encompassing studies in both Indonesian and English. The chosen data analysis technique for this study is content analysis, providing a methodological approach to systematically examine and interpret the content of the gathered materials.